2015
DOI: 10.1016/j.freeradbiomed.2015.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary nitrate supplementation on the oxygen cost of exercise and walking performance in individuals with type 2 diabetes: a randomized, double-blind, placebo-controlled crossover trial

Abstract: Dietary nitrate supplementation has been shown to reduce the oxygen (O2) cost of exercise and enhance exercise tolerance in healthy individuals. This study assessed whether similar effects could be observed in individuals with type 2 diabetes (T2DM). In a randomized, double-blind, placebo-controlled crossover study, 48 participants with T2DM supplemented their diet for 4 days with either nitrate-rich beetroot juice (70ml/day, 6.43mmol nitrate/day) or nitrate-depleted beetroot juice as placebo (70ml/day, 0.07mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 73 publications
5
32
2
Order By: Relevance
“…In a further crossover study in 48 patients with type 2 diabetes mellitus, not included in this analysis, Shepherd et al . found that 4 days' supplementation with nitrate‐rich beetroot juice did not reduce the O 2 cost of walking or the distance covered in a 6MWT compared to placebo . There were also no effects seen with blood pressure.…”
Section: Does Nitrite Alter Mitochondrial Metabolism?mentioning
confidence: 93%
“…In a further crossover study in 48 patients with type 2 diabetes mellitus, not included in this analysis, Shepherd et al . found that 4 days' supplementation with nitrate‐rich beetroot juice did not reduce the O 2 cost of walking or the distance covered in a 6MWT compared to placebo . There were also no effects seen with blood pressure.…”
Section: Does Nitrite Alter Mitochondrial Metabolism?mentioning
confidence: 93%
“…This ʻnitrate–nitrite–NO pathwayʼ appears to lack these tolerance issues , and to suppress ROS and reverse endothelial dysfunction , and has been extensively investigated clinically in studies up to 4–6 weeks, particularly for BP lowering . By contrast, patients with T2DM appear to lack any effect of dietary nitrate on BP .…”
Section: Introductionmentioning
confidence: 99%
“…This ʻnitrate-nitrite-NO pathwayʼ appears to lack these tolerance issues [14], and to suppress ROS [15] and reverse endothelial dysfunction [16], and has been extensively investigated clinically in studies up to 4-6 weeks, particularly for BP lowering [14,[16][17][18][19]. By contrast, patients with T2DM appear to lack any effect of dietary nitrate on BP [19][20][21]. However, we recently reported (with the main haemodynamic findings of the current study) that dietary nitrate lowered central aortic systolic BP {SBP; mean À2.6 [95% confidence interval (CI) À4.5, À0.75] mm Hg; p = 0.007}, despite no effect on brachial BP [22].…”
Section: Introductionmentioning
confidence: 99%
“…This appears to provide an alternative source of NO when endogenous synthesis through the oxygen‐dependent l ‐arginine NO synthase pathway is impaired. Trials of supplementation have suggested that adding nitrate to the diet can lower blood pressure, reduce the oxygen cost of exercise, and protect against ischemia–reperfusion injury, although not all studies report such changes …”
Section: Introductionmentioning
confidence: 99%
“…Trials of supplementation have suggested that adding nitrate to the diet can lower blood pressure, reduce the oxygen cost of exercise, and protect against ischemiareperfusion injury, 4 although not all studies report such changes. 5 The potential benefits of nitrate from the diet have led to calls from some quarters to raise the recommended daily intake. There do, however, remain a number of significant unanswered questions in the field.…”
mentioning
confidence: 99%